2022
DOI: 10.3390/life12081162
|View full text |Cite
|
Sign up to set email alerts
|

Recapsoma®: A Novel Mixture Based on Bergamot, Ipomoea Batatas, Policosanol Extracts and Liposomal Berberine for the Treatment of Hypercholesterolemia

Abstract: Cardiovascular disease (CVD) is considered one of the major causes of mortality worldwide. Epidemiological studies have shown that regular consumption of phenols is inversely associated with cardiovascular disease, and the use of nutraceuticals and functional foods can provide protective, preventive, and possibly curative effects in CVD. A novel mixture of different natural substances named Recapsoma® (bergamot, liposomal berberine, Ipomoea batatas, oleuropein, polycosanols, and vitamin E) has been produced, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Lipid nanoparticles are bioactive carrier systems that can improve transport, pharmacokinetics, and stability of encapsulated nutraceuticals; nanoemulsions and microemulsions have also been employed [46]. These formulations have been utilized to deliver nutraceuticals for the treatment of hypercholesterolemia in adult subjects, such as polyphenols and bergamot [47]. Some, but not all, guidelines for dyslipidemia include nutraceuticals among potentially effective treatment options for mild dyslipidemia.…”
Section: Nutraceuticals In the Treatment Of Familial Hypercholesterol...mentioning
confidence: 99%
“…Lipid nanoparticles are bioactive carrier systems that can improve transport, pharmacokinetics, and stability of encapsulated nutraceuticals; nanoemulsions and microemulsions have also been employed [46]. These formulations have been utilized to deliver nutraceuticals for the treatment of hypercholesterolemia in adult subjects, such as polyphenols and bergamot [47]. Some, but not all, guidelines for dyslipidemia include nutraceuticals among potentially effective treatment options for mild dyslipidemia.…”
Section: Nutraceuticals In the Treatment Of Familial Hypercholesterol...mentioning
confidence: 99%
“…It contains abundant nutrients, including protein, carbohydrates, minerals, vitamins, carotenoids, dietary fber, and polyphenols. Previous studies have reported that sweet potato has many benefcial efects such as antioxidation [5][6][7], anticancer [8,9], anti-infammatory [10], liver protection [11], and prevention of cardiovascular disease [12]. Owing to its nutritional components and agronomic advantages, sweet potato could help prevent and reduce mal-or overnutrition in developing and developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), cardiovascular diseases (CVDs) are the leading cause of mortality, both in industrialized and developing countries [ 1 ]. In 2019, around 17.9 million people died from CVDs, representing 32% of deaths world-wide.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, around 17.9 million people died from CVDs, representing 32% of deaths world-wide. By 2030, it is estimated that at least 24 million people may die mainly from heart attack or stroke [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%